Представьте в виде произведения выражение: (4x-9)^2-(2x+19)^2; (a+b+c)^2-(a-b-c)^2 . Пожалуйста напишите решение
Представьте в виде произведения выражение: (4x-9)^2-(2x+19)^2; (a+b+c)^2-(a-b-c)^2 . Пожалуйста напишите решение
Ответ(ы) на вопрос:
1)
[latex](4x-9)^2-(2x+19)^2=(4x-9+2x+19)(4x-9-2x-19)=[/latex][latex]=(6x+10)(2x-28)=2*(3x+5)*2(x-14)=4(3x+5)(x-14)[/latex]
2)
[latex](a+b+c)^2-(a-b-c)^2=(a+b+c+a-b-c)*[/latex][latex]*(a+b+c-a+b+c)=2a(2b+2c)=2a*2(b+c)=4a(b+c)[/latex]
формула a²-b²=(a-b)(a+b)
(4x-9)²-(2x+19)²=( (4x-9)-(2x+19)) *( (4x-9)+(2x+19))=
=(4x-9-2x-19)*(4x-9+2x+19)=(2x-28)(6x+10)
(a+b+c)²-(a-b-c)²= ( (a+b+c)-(a-b-c))*( (a+b+c)+(a-b-c))=
=(a+b+c-a+b+c)*(a+b+c+a-b-c)=(2b+2c)*2a
Не нашли ответ?
Похожие вопросы